Blinded, Randomized, Controlled Trial Evaluating the Effects of Light-Emitting Diode Photomodulation on Lower Extremity Wounds Left to Heal by Secondary Intention. Issue 5 (May 2020) - Perper, Marina; Eber, Ariel; Lindsey, Scott F.; Nouri, Keyvan
Abstract : BACKGROUND: Light-emitting diode (LED) has been used for wound healing because of its stimulatory effects on fibroblast proliferation, matrix synthesis, angiogenesis, and downmodulation of inflammatory reactions. OBJECTIVE: The aim of the authors' study was to investigate the effects of red LED (wavelength 633 nm) photomodulation on lower extremity surgical defects left to heal by secondary intention. MATERIALS AND METHODS: Fourteen subjects with surgical defects of the lower leg were irradiated with a 633 ± 3-nm light source for 20 minutes (105 mW/cm 2, 126 J/cm 2 ) at 4 weekly sessions. RESULTS: The number of days required for wounds to heal was greater in the treatment group (63.2 ± 12.2 days) than in the control group (48.67 ± 11.1 days), although this difference was not statistically significant ( p = .07). The percentage of the original wound remaining was not statistically different between treatment and control groups between Weeks 1 and 2 ( p = .71) and Weeks 3 and 4 ( p = .56). It was significant between Weeks 2 and 3 ( p = .01). CONCLUSION: This study revealed that red LED photomodulation at a wavelength of 633 nm did not result in clinical improvement in wound healing of surgical defects on the lower extremities.